2015
DOI: 10.1186/s13054-015-1105-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal therapies in pediatric severe sepsis: findings from the pediatric health-care information system

Abstract: IntroductionPediatric severe sepsis (PSS) continues to be a major health problem. Extracorporeal therapies (ETs), defined as extracorporeal membrane oxygenation (ECMO) and RRenal replacement therapyenal replacement therapy (RRT), are becoming more available for utilization in a variety of health conditions. We aim to describe (1) rates of utilization of ET in PSS, (2) outcomes for PSS patients receiving ET, and (3) epidemiologic characteristics of patients receiving ET.MethodsWe conducted a retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
9
58
0
3
Order By: Relevance
“…As such, children with life-threatening sepsis-induced ARDS are often considered as candidates for ECMO rescue [477], and PALICC endorsed ECMO for the treatment of refractory hypoxia [24]. The use of ECMO in pediatric sepsis has increased over the past decade [478,479]; whether this has improved survival remains to be determined [480]. To date, no RCT examining the effect of ECMO on outcome in pediatric sepsis has been published.…”
Section: We Suggest Using Venovenous Ecmo In Children With Sepsis-indmentioning
confidence: 99%
“…As such, children with life-threatening sepsis-induced ARDS are often considered as candidates for ECMO rescue [477], and PALICC endorsed ECMO for the treatment of refractory hypoxia [24]. The use of ECMO in pediatric sepsis has increased over the past decade [478,479]; whether this has improved survival remains to be determined [480]. To date, no RCT examining the effect of ECMO on outcome in pediatric sepsis has been published.…”
Section: We Suggest Using Venovenous Ecmo In Children With Sepsis-indmentioning
confidence: 99%
“…Despite limited data specific for the neonatal septic population, utilization of adjunctive extracorporeal techniques during ECMO has become standard practice. In a retrospective analysis of pediatric admissions for sepsis between 2004 and 2012 collected via Pediatric Health Information System (PHIS), 169 children under 1 year of age received both ECMO and renal replacement therapy (RRT) (58). Hypoxia, arterial hypotension, low cardiac output state, diastolic steal via PDA, and high vasoactive support can lead to acute kidney injury (AKI) in neonates with sepsis (59).…”
Section: Role Of Adjunctive Extracorporeal Therapiesmentioning
confidence: 99%
“…A previous study reviewed the characteristics of patients with pediatric burn sepsis, including patient categorization, diagnosis and treatment and it was identified that the mortality rate of pediatric patients with burn sepsis is significantly higher mortality than that of adult patients (4). Although an increasing number of strategies have been explored for the treatment of pediatric burn sepsis, the mortality rate remains high (5,6). Additionally, the physiological characteristics, drug treatment and inflammatory responses to burn injury in pediatric patients differ significantly compared with those in adult patients (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%